Applying the S-ART Framework to Yoga: Exploring the Self-Regulatory Action of Yoga Practice in Two Culturally Diverse Samples - Tolbaños-Roche, Laura; Menon, Praseeda (Frontiers in Psychology, 2021)
Mindfulness practices form the core of numerous therapeutic programmes and interventions for stress reduction and treatment of different health conditions related to stress and life habits. Ways and means to regulate one-self effectively also form the foundation of the path of yoga in the accomplishment of holistic health and well-being. The S-ART (Self -awareness, -regulation, -transcendence) model can be considered as an overarching neuro-biological framework to explain self-regulatory mechanisms of well-being present in mindfulness-based practices. The current study, by connecting and applying the S-ART framework to self-regulatory mechanisms in yoga and generating related hypotheses, provides a theory-led explanation of the action of yoga practices, which is sparse in the literature. Testing the S-ART model in yoga in two culturally diverse samples, assessing model-mapped psychological mechanisms of action, and exploring the influence of perseverance in yoga practice are original contributions of the study. The study sample comprised 362 yoga practitioners and non-practitioners (197 Indian, 165 Spanish), who completed four tests of psychological variables indicative of the aforementioned three S-ART abilities. These tests were Multidimensional Assessment of Interoceptive Awareness, Experiences Questionnaire-Decentering subscale, Difficulties in Emotion Regulation Scale, and Relational Compassion Scale. Results indicated significantly better self-awareness and self-regulatory abilities in yoga practitioners (Indian and Spanish combined) than non-practitioners, reflected in higher levels of interoceptive awareness and decentering abilities. Moreover, perseverance in yoga practice acted as a significant predictor of self-awareness and self-regulation in practitioners. Analysis of each cultural sample revealed some differences. Yoga practice and perseverance in it acted as a significant predictor of interoceptive awareness and decentering in Indian practitioners having more than 1 year of sustained yoga practice, but for the Spanish participants, Physical Exercise and Frequency of Yoga Practice acted as better predictors of interoceptive awareness and decentering than yoga practice and perseverance in it. The results obtained suggested that the S-ART model provided preliminary but promising evidence for the self-regulatory mechanisms of action of yoga practice within a culturally diverse sample of yoga practitioners. This study also widens the scope of further hypothesis generation using the S-ART theoretical framework for testing self-regulatory mechanisms of action in yoga practice.